IMPLEMENTASI SINERGI BURUAN SAE DAN PMT POSYANDU DALAM PENGUATAN KETAHANAN PANGAN, PERBAIKAN GIZI, DAN EKONOMI PRODUKTIF MASYARAKAT DI KAMPUNG BENGKOK RW. 001 KELURAHAN CIUMBULEUIT KECAMATAN CIDADAP, KOTA BANDUNG - Somantri, Asep (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2025)
The Buruan Sae program initiated by the Bandung City Government aims to strengthen community food security through productive use of home gardens. At the same time, the Supplementary Feeding Program (PMT) at local Posyandu plays a vital role in improving child nutrition. The synergy between these two initiatives is particularly significant, as harvests from Buruan Sae not only enhance the availability of healthy food but also supply raw materials for PMT while creating opportunities for community-based economic activities. This community service program was conducted in Kampung Bengkok RW 001, Ciumbuleuit Village, Cidadap District, Bandung City, with the objectives of reinforcing household food security, improving community nutrition, and fostering financial independence among residents. The implementation methods included socialization, urban farming training, mentoring on the use of harvests for Posyandu PMT, and facilitation of value-added product development. The results indicated increased awareness among residents regarding diversified, nutritious, balanced, and safe diets (B2SA), improved availability of fresh vegetables for households and PMT, and community initiatives to process surplus harvests into marketable products. These findings highlight that the integration of Buruan Sae and Posyandu PMT not only contributes to food security and child nutrition but also promotes sustainable, community-based economic productivity.